"Smart traffic light" ("Smart traffic light") in order to prevent traffic jams at intersections - Nematov Abdugani; Sadikov Rustamjon Toxirovich; Ismoilov Shikhnazar Rashid ugli (Global Scientific Publishing, 2024)
In this article, we examine the various tasks and functions of intelligent traffic lights that contribute to their effectiveness in preventing congestion at intersections. From traffic monitoring and dynamic signal timing, to pedestrian safety prioritization and seamless integration with wider traffic management systems, smart traffic lights play an important role in improving traffic efficiency and ensuring smooth, sustainable traffic in cities. Let's take a closer look at how devices are revolutionizing the way we approach traffic management at intersections.
Keywords: traffic; smart traffic lights